Building the data warehouse - Inmon, William H.
The new edition of the classic bestseller that launched the data warehousing industry covers new approaches and technologies, many of which have been pioneered by Inmon himself. In addition to explaining the fundamentals of data warehouse systems, the book covers new topics such as methods for handling unstructured data in a data warehouse and storing data across multiple storage media. Discusses the pros and cons of relational versus multidimensional design and how to measure return on investment in planning data warehouse projects. Covers advanced topics, including data monitoring and testing